LEGISLATIVE ELECTIONS: AN OVERVIEW OF CLOSED PROPORTIONAL SYSTEM - Muhammad Mutawalli; Maskun; Zainal Amin Ayub; Muhammad Saleh Tajuddin; Harlida Abdul Wahab (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
This study aims to analyze the constitutionality of legislative general elections with a review of the closed proportional system in the 1945 Constitution. The legislative election system is an important tool for maintaining democratic principles and fair representation in a country. The constitutionality of the closed proportional system has been the subject of ongoing debate. This study uses a qualitative approach with normative juridical methods to analyze the constitutionality of general legislative elections that use a closed proportional system. This approach involved collecting data from legal documents, literature studies, and court decisions that were relevant to this topic. The results of the study showed that the application of a closed proportional system in legislative general elections has several constitutional implications, such as the limitation of political access for individuals outside of political parties, which can be considered as a violation of the individual's constitutional right to participate in the political process. This research also showed that a closed proportional system can provide greater political stability and strengthen the role of political parties in the political system. This study also analyzed the implications of implementing an open proportional system in legislative general elections. Abstrak: Penelitian ini bertujuan untuk mengkaji konstitusionalitas pemilihan umum legislatif dengan tinjauan terhadap sistem proporsional tertutup dalam UUD 1945. Sistem pemilihan umum legislatif adalah aspek penting dalam menjaga prinsip demokrasi dan keterwakilan yang adil dalam sebuah negara. Sistem proporsional tertutup telah menjadi subjek perdebatan yang berkelanjutan mengenai konstitusionalitasnya dalam konteks UUD 1945. Penelitian ini menggunakan pendekatan kualitatif dengan metode yuridis normatif untuk menganalisis konstitusionalitas pemilihan umum legislatif dengan menggunakan sistem proporsional tertutup. Pendekatan ini melibatkan pengumpulan data dari dokumen hukum, studi literatur, dan putusan pengadilan yang relevan dengan topik ini. Hasil penelitian menunjukkan bahwa penerapan sistem proporsional tertutup dalam pemilihan umum legislatif memiliki beberapa implikasi konstitusional. Pertama, sistem ini dapat membatasi akses politik bagi individu di luar partai politik, yang dapat dianggap sebagai pelanggaran terhadap hak konstitusional individu untuk berpartisipasi dalam proses politik. Penelitian ini juga menganalisis implikasi penerapan sistem proporsional terbuka dalam pemilihan umum legislatif. Penelitian ini juga menunjukkan bahwa sistem proporsional tertutup dapat memberikan stabilitas politik yang lebih besar dan memperkuat peran partai politik dalam sistem politik. Kata Kunci: Konstitusionalitas, Pemilihan Umum Legislatif, Sistem Proporsional Tertutup, UUD 1945, Kebebasan Politik